Scintillation Response Enhancement in Nanocrystalline Lead Halide Perovskite Thin Films on Scintillating Wafers - Kateřina Děcká; Jan Král; František Hájek; Petr Průša; Vladimir Babin; Eva Mihóková; Václav Čuba (Nanomaterials, 2021)
Lead halide perovskite nanocrystals of the formula CsPbBr3 have recently been identified as potential time taggers in scintillating heterostructures for time-of-flight positron emission tomography (TOF-PET) imaging thanks to their ultrafast decay kinetics. This study investigates the potential of this material experimentally. We fabricated CsPbBr3 thin films on scintillating GGAG:Ce (Gd2.985Ce0.015Ga2.7Al2.3O12) wafer as a model structure for the future sampling detector geometry. We focused this study on the radioluminescence (RL) response of this composite material. We compare the results of two spin-coating methods, namely the static and the dynamic process, for the thin film preparation. We demonstrated enhanced RL intensity of both CsPbBr3 and GGAG:Ce scintillating constituents of a composite material. This synergic effect arises in both the RL spectra and decays, including decays in the short time window (50 ns). Consequently, this study confirms the applicability of CsPbBr3 nanocrystals as efficient time taggers for ultrafast timing applications, such as TOF-PET.